The Impact of Educational Facilities on Student Motivation in Elementary School - Akmal, Fauzi; Taqiyuddin, Muhammad Fikri (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2024)
This study aims to determine the effect of facilities and infrastructure (x) on student learning motivation (y). This study is a quantitative study using a product moment analysis research design. The data collection techniques used in this study were questionnaires and documentation. The subjects in this study were all 57 students in grades IV-VI. Data analysis was performed manually using Microsoft Excel and SPSS 26 software. The results of this study are as follows: i) The facilities and infrastructure available in elementary schools are considered good, as indicated by a mean or average score of 46.7, which falls within the 45-51 interval, with a standard deviation of 4.62, representing a result of 56%. ii) The learning motivation of elementary school students is classified as poor, as seen from the mean or average value of 46 with a standard deviation of 5.24, which is presented as a result of 44%. iii) There is an influence between the facilities and infrastructure variable (x) and student learning motivation (y) based on the simple linear regression formula. The data obtained shows a sig of 0.000<0.05 (5% significance level), so Ha is accepted and Ho is rejected. Furthermore, based on data analysis, it is known that there is an R Square of 0.355 x 100% = 35.5%. This indicates that there is an influence between facilities and infrastructure (x) on learning motivation.